1985
DOI: 10.1111/j.1440-6055.1985.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

A WIND‐ORIENTED FLY TRAP FOR QUANTITATIVE SAMPLING OF ADULT MUSCA VETUSTISSIMA WALKER

Abstract: A wind-oriented bait trap is described for sampling populations of bush fly (Musca i,eiustissima). The trap is less costly than the current "West Australian" blowfly trap, easier to maintain and operate. but samples just as effectively. The trap is baited with a mixture of cattle dung. minced liver, and sodium sulphide. in which blowfly larvae have developed for 2-3 d at 26 C. The function of the larvae is to maintain the attractiveness ofthe bait at a constant level for up to 2 d in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…Regarding the other dominant families in the carrion fly assemblages, female-biased captures were reported in Muscidae (Vogt et al 1985a; Patitucci et al 2010), but no significant differences in the age composition of the collected females were observed (Tyndale-Biscoe and Hughes 1969). In the case of Sarcophagidae, several studies showed a higher proportion of females captured by using different types of carrion-baited traps (Martínez-Sánchez et al 2000; Romera et al 2003).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding the other dominant families in the carrion fly assemblages, female-biased captures were reported in Muscidae (Vogt et al 1985a; Patitucci et al 2010), but no significant differences in the age composition of the collected females were observed (Tyndale-Biscoe and Hughes 1969). In the case of Sarcophagidae, several studies showed a higher proportion of females captured by using different types of carrion-baited traps (Martínez-Sánchez et al 2000; Romera et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…The use of odor and carrion bait is a widely used practice in the study of sarcosaprophagous Diptera, and there is a large variety of effective carrion-baited trap designs (e.g., Vogt et al 1985a; Schoenly et al 1991; Hwang and Turner 2005; Baz et al 2007). However, the sampling of sarcosaprophagous flies with the use of carrion-baited traps could imply different areas of bias (Hwang and Turner 2005), which must be taken into account when analyzing the results of the captures.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the specimens deposited in CEUA and IVIC were collected by the authors using (WOT)Wind Oriented Traps baited with fish and pig liver (see Vogt et al 1985). The classification used in the checklist follows Rognes (1986, 1991, 1997) and Marinho et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the other dominant families in the carrion fly assemblages, female-biased captures were reported in Muscidae (Vogt et al 1985a;Patitucci et al 2010), but no significant differences in the age composition of the collected females were observed (Tyndale-Biscoe and Hughes 1969). In the case of Sarcophagidae, several studies showed a higher proportion of females captured by using different types of carrion-baited traps (Martínez-Sánchez et al 2000;Romera et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The use of odor and carrion bait is a widely used practice in the study of sarcosaprophagous Diptera, and there is a large variety of effective carrion-baited trap designs (e.g., Vogt et al 1985a;Schoenly et al 1991;Hwang and Turner 2005;Baz et al 2007).…”
Section: Introductionmentioning
confidence: 99%